Short-term Cost-effectiveness of Reteplase versus Primary Percutaneous Coronary Intervention in Patients with Acute STEMI a Tertiary Hospital in Iran - Alimohammadzadeh, Khalil; Sadeghi, Roxana; Maher, Ali; Kazemi, Mohammad Kazem (International Journal of Cardiovascular Practice, 2017)
Â Â Introduction: This study aimed to compare primary percutaneous coronary intervention (PPCI) versus reteplase in terms of clinical and para-clinical outcomes; as well as cost-effectiveness in patients with ST-segment-elevation myocardial infarction (STEMI).Primary percutaneous coronary intervention is the method of choice in all patients especially those at higher risks. But an on-site professional team in a 24/7 facilitated system is a difficult goal to achieve in many areas and countries, therefore the cost-effectiveness of these two treatment strategies (PPCI and reteplase) needs to be discussed.Methods: This prospective cohort study included 220 patients presented with STEMI who were admitted to a university hospital between January 2014 to July 2016. Patients were divided into two groups of 120, either receiving reteplase or PPCI. Clinical outcomes were considered duration of hospital stay and MACE (Major Advanced Cardiovascular Events) including death, cerebrovascular accident, need for repeat revascularization, and major bleeding. LVEF (Left ventricular ejection fraction) was considered as a para-clinical outcome. The outcomes and total hospital cost were compared between two treatment groups.Results: Demographic characteristics between two groups of PPCI or reteplase didnât show any significant differences. But in para-clinical outcomes, patients in PPCI group showed higher LVEF, compared with reteplase group (45.9 Â± 11.5% versus 42.0 Â± 11.8%; P = 0.02). Complication rates were similar in both groups but repeat revascularization or coronary artery bypass surgery was more prevalent in those who received thrombolytic therapy (P < 0.05). Length of hospital stay in both groups was similar in two groups but total cost was higher in patients who have received PPCI. (147769406.9 Â± 103929358.9 Tomans vs. 117116656.9 Â± 67356122.6 Tomans; respectively, P = 0.01).Conclusions: In STEMI patients who present during off-hours, thrombolytic therapy seems to represent a safe alternative to PPCI. Higher costs for patients with PPCI may be decreased with shorter duration of hospital stays according to guidelines.